ACTUARIAL STUDY OF DEMOGRAPHIC FACTORS CONTRIBUTING TO THE HIGHER RETIREMENT AGE - A. K. Soloviev; B. Y. Popov (Финансы: теория и практика, 2017)
Traditionally, the increase in life expectancy at the birth rate prevailing over the last decade is considered as a main argument for rising the retirement age in Russia. However, this demographic indicator either from methodological or practical position is not a parametric characteristic of modern pension system which operates on the basis of market mechanisms of insurance. The characteristics which are really important for the pension scheme and the implementation of government pension obligations include: mortality rates by age groups, duration of the period after granting of a non-contributory pension, healthy lifespan. Unfortunately, the supporters of “budget savings at the expense of retirees” fully ignore the mentioned indicators. The author carries out a comprehensive analysis of the impact of demographic factors on the retirement age under the non-contributory pension plan. Such indicator as the “retirement age” should be seen only in economic sense and act as an insurance standard which along with the above mentioned normative parameters of the non-contributory pension system would create conditions for state regulation of the actuarial balance between the pension rights of insured persons and government obligations to provide an adequate financial security of life for people who have left their work.